The role of MRI in assessing cognitive impairment changes - Ahmad, Doha Jamal; Alghamdi, Ahmed Abdullah; Alshahrani, Nada Aeydh; Albarrati, Fatimah Mofareh; Alshehri, Sarah Ali; Talbi, Nouf Essa; Alshehri, Mohammed Fadhel; Alomani, Najla Juma; Alshehri, Israa Hamdan; Hutaylah, Hussain Hatim Al; Alghanmi, Mohammad Dakhilalla (International Journal Of Community Medicine And Public Health, 2023)
Aging brings about various changes in the brain, leading to cognitive alterations that are increasingly relevant with extended life expectancy. Dementia, characterized by chronic cognitive impairment, is on the rise due to longer life expectancy, imposing a substantial burden on healthcare systems. Dementia encompasses conditions like Alzheimer's disease (AD), vascular dementia (VaD), Lewy body dementia (LBD), and frontotemporal dementia, each with its distinct symptoms and progression. Magnetic resonance imaging (MRI), especially 3T MRI, plays a crucial role in monitoring and diagnosing dementia, aiding in patient selection for emerging therapies. Study involves a comprehensive literature search without restrictions on date, language, age/publication type. Dementia can be divided into neurodegenerative and nondegenerative categories, with AD being the most prevalent. Diagnosis relies on clinical evaluation, supported by neuroimaging techniques like MRI. Various MRI findings, such as cerebral atrophy, microbleeds, white matter hyperintensities, lacunes, and strategic infarcts, offer insights into dementia-related brain changes. These findings facilitate early diagnosis, prognosis, and treatment monitoring, with standardized assessment tools and volumetric analysis enhancing diagnostic accuracy. As life expectancy continues to rise, MRI's role in assessing cognitive impairment changes becomes increasingly vital in addressing the growing challenge of dementia.